2020
DOI: 10.5194/essd-2020-355
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Changes in China's anthropogenic emissions during the COVID-19 pandemic

Abstract: Abstract. The COVID-19 pandemic lockdowns led to a sharp drop in socio-economic activities in China in 2020, including reductions in fossil fuel use, industry productions, and traffic volumes. The short-term impacts of lockdowns on China's air quality have been measured and reported, however, the changes in anthropogenic emissions have not yet been assessed quantitatively, which hinders our understanding of the causes of the air quality changes during COVID-19. Here, for the first time, we report the anthropog… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…A sudden decline in the meteorologically normalized NO 2 coincided with the start of the CSF in all studied cities in 2015–2019 (Figure ), with an average PCSF of −14.1%, ranging from −24.1 ± 2.0% in Hangzhou to −3.9 ± 1.1% in Harbin (Table ). A recent study reported that the CSF effect caused a 20.9% reduction of the NO x emission intensity (Gg/d) in China in 2019 (Zheng et al., 2020), comparable to our estimates of NO 2 in 2019 (14.7 ± 6.5%). On average, O 3 increased by 6.6% (from +1.5 ± 3.4% in Lhasa to +10.0 ± 1.4% in Changchun) (Figure ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A sudden decline in the meteorologically normalized NO 2 coincided with the start of the CSF in all studied cities in 2015–2019 (Figure ), with an average PCSF of −14.1%, ranging from −24.1 ± 2.0% in Hangzhou to −3.9 ± 1.1% in Harbin (Table ). A recent study reported that the CSF effect caused a 20.9% reduction of the NO x emission intensity (Gg/d) in China in 2019 (Zheng et al., 2020), comparable to our estimates of NO 2 in 2019 (14.7 ± 6.5%). On average, O 3 increased by 6.6% (from +1.5 ± 3.4% in Lhasa to +10.0 ± 1.4% in Changchun) (Figure ).…”
Section: Resultssupporting
confidence: 91%
“…The declines in NO 2 were strongly related to transportation and industrial emission changes as determined by the changes in anthropogenic emissions in February 2019 in mainland China (Zheng et al., 2020). Such effects of CSF on NO 2 were more substantial for cities with greater vehicle populations (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The mass concentration of PM 2.5 was determined using an oscillating balance analyzer (TH-2000Z, China) (Wang et al, 2014). The NH 3 concentration and watersoluble ions including sulfate (SO 2− 4 ), nitrate (NO − 3 ), ammonium (NH + 4 ), sodium ion (Na + ), and chloridion (Cl − ) were monitored with a gas and aerosol collector combined with ion chromatography (GAC-IC; TH-PKU-303, China) (Wang et al, 2014;Zheng et al, 2019). Organic carbon (OC) and elemental carbon (EC) were measured using an OC-EC analyzer (model RT-4, Sunset Laboratory Inc., Tigard, Oregon, USA).…”
Section: Field Observationmentioning
confidence: 99%
“…However, both observed NO − 3 and NH + 4 concentrations in Tangshan even showed slight increases, though the NO 2 concentration suffered from a remarkable decrease. It was assumed that the adverse meteorological conditions might be beneficial to the pollutant accumulation (Zheng et al, 2019;. Additionally, the concentrations of nine trace elements were also determined.…”
Section: Source Apportionmentmentioning
confidence: 99%
See 1 more Smart Citation